Highly efficient and selective anticancer approach through acrolein-triggered cycloaddition chemistry in patient-derived xenografts: Mechanistic and preclinical investigation - Yuria Takahashi; Kazuki Terashima; Taiji Shimoda; Masayuki Nagahashi; Koji Morimoto; Sayaka Urano; Kozo Kataoka; Hisashi Shinohara; Yasuo Miyoshi; Ambara R. Pradipta; Katsunori Tanaka (Tetrahedron Chem, 2024)
The efficacy of anticancer treatments in the clinical setting can be improved by decreasing off-target effects. Chemistry-based methods are emerging as a promising strategy to overcome this limitation. We previously developed a prodrug strategy using mitomycin C (MMC) activated at the tumor site by the [3 + 2] cycloaddition of endogenous acrolein, which is overexpressed in various cancers. Herein, we report the results of mechanistic and preclinical studies using a prodrug of doxorubicin (DOX), which is used in the treatment of several cancers, but its dosage is restricted by off-target effects. First, we developed robust chemistry methods for the synthesis of large amounts of prodrug for animal experiments. The DOX prodrug showed high anticancer efficacy without off-target effects even at high doses. Pharmacokinetic/pharmacodynamic, biodistribution, and serum protein binding studies supported the in vivo anticancer efficacy of DOX derivatization with the hydrophobic 2,6-diisopropyl azidobenzylcarbamate protecting group. This enhanced albumin binding, thereby increasing circulatory residence (serum stability). The stabilized prodrug could only be activated at the tumor site by reacting with endogenous acrolein to gradually release the required amounts of drug. Inhibiting overproduction of the drug and its circulation back into the blood minimized off-target effects. Nonspecific organ accumulation was not observed, supporting the safety of the prodrug in vivo. DOX and MMC prodrugs showed selective anticancer efficacy against patient-derived samples from lung, colorectal, gastric, and breast cancers. The proposed in vivo chemical strategy should be tested in clinical trials in the future.